PRICE DISCOUNT, SALES PROMOTION DAN BONUS PACK TERHADAP IMPULSE BUYING PADA PT MATAHARI DEPARTEMENT STORE MAKASSAR - Orfiyanny S.Themba (AkMen JURNAL ILMIAH, 2019)
The purpose of this research is to know the simultaneous and partial influence between price discount, sales promotion and bonus pack to impulse buying. As quantitative research, a survey method using a questionnaire was used. The sampling technique was purposive sampling and accidental sampling. The population in this research someone that were buying in PT Matahari Departement Store, Tbk Makassar. The sample was 90 respondents. Methods of data analysis using is descriptive analysis and multiple regression techniques. The results showed that price discount, sales promotion and bonus pack influenced positive and significant on impulse buying.